Parametric Marcinkiewicz Integral and Its Higher-Order Commutators on Variable Exponents Morrey-Herz Spaces - Omer Abdalrhman Omer; Khedoudj Saibi; Muhammad Zainul Abidin; Mawia Osman (Journal of Function Spaces)
In this article, we prove the boundedness of the parametric Marcinkiewicz integral and its higher-order commutators generated by BMO spaces on the variable Morrey-Herz space. All the results are new even when α· is a constant.